2013
DOI: 10.1590/s2238-10312013000200010
|View full text |Cite
|
Sign up to set email alerts
|

The impact of thermal comfort in the perceived level of service and energy costs of three Brazilian airports

Abstract: To evaluate airports’ current thermal comfort temperature and humidity were registered in three main Brazilian international airports, other variables were local region climate characteristics and the constructive types of passenger terminal buildings. The Brazilian air transportation demand has considerably grown over the last decade, with some airports reaching their capacity. Thermal discomfort may be a key driver of passenger perceptions of airport service levels, specially under capacity overload situatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…For precipitation, we detected a slight difference in a few days of the control period. Considering that precipitation is an important factor that influences the dilution and dispersion of pollutants [69][70][71][72], a 12-day control period with precipitation above 10 mm was not considered in this study. After excluding these outlier days, we observed that the means and ranges of meteorological variables were similar over the weeks of the quarantine and control periods (Table 2).…”
Section: Air Quality Improvement During 90 Days Of Covid-19 Social Di...mentioning
confidence: 99%
“…For precipitation, we detected a slight difference in a few days of the control period. Considering that precipitation is an important factor that influences the dilution and dispersion of pollutants [69][70][71][72], a 12-day control period with precipitation above 10 mm was not considered in this study. After excluding these outlier days, we observed that the means and ranges of meteorological variables were similar over the weeks of the quarantine and control periods (Table 2).…”
Section: Air Quality Improvement During 90 Days Of Covid-19 Social Di...mentioning
confidence: 99%
“…For precipitation, we detected a discrepancy ( Table 1). Considering that precipitation is an important factor that influences the dilution and dispersion of pollutants (Chou et al, 2005;Pellon de Miranda et al, 2004;Ramis and Santos, 2013;Yu, 2012), 12 days of control period, with precipitation above 10 mm, were not considered in this study. After excluding these outlier days, we can observe that the means and ranges of meteorological variables were similar over the weeks of the quarantine and control period ( Table 2).…”
Section: Air Quality Improvement During 90 Days Of Covid-19 Social DImentioning
confidence: 99%
“…However, it was seen that increasing natural ventilation in the summer significantly decreases the cooling load but increases the heating load in the winter. Ramis and Santos (2013) evaluated the thermal comfort levels based on the measurements conducted at the three largest airports in Brazil. The study showed that the best thermal comfort level was achieved in types of buildings where natural air circulation takes place based on the temperature and humidity measurements.…”
Section: Introductionmentioning
confidence: 99%